Suppression on Your Own Terms - Sayers, W. Michael; Sayette, Michael A. (Psychological Science, 2013)
Research on emotion suppression has shown a rebound effect, in which expression of the targeted emotion increases following a suppression attempt. In prior investigations, participants have been explicitly instructed to suppress their responses, which has drawn the act of suppression into metaconsciousness. Yet emerging research emphasizes the importance of nonconscious approaches to emotion regulation. This study is the first in which a craving rebound effect was evaluated without simultaneously raising awareness about suppression. We aimed to link spontaneously occurring attempts to suppress cigarette craving to increased smoking motivation assessed immediately thereafter. Smokers ( n = 66) received a robust cued smoking-craving manipulation while their facial responses were videotaped and coded using the Facial Action Coding System. Following smoking-cue exposure, participants completed a behavioral choice task previously found to index smoking motivation. Participants evincing suppression-related facial expressions during cue exposure subsequently valued smoking more than did those not displaying these expressions, which suggests that internally generated suppression can exert powerful rebound effects.